Beauveria bassiana (Balsamo) Vuillemin as an endophyte in tissue culture banana (Musa spp.) - Akello, Juliet; Dubois, Thomas; Gold, Clifford S.; Coyne, Daniel; Nakavuma, Jessica; Paparu, Pamela (Journal of invertebrate pathology, 2007)
Beauveria bassiana is considered a virulent pathogen against the banana weevil Cosmopolites sordidus. However, current field application techniques for effective control against this pest remain a limitation and an alternative method for effective field application needs to be investigated. Three screenhouse experiments were conducted to determine the ability of B. bassiana to form an endophytic relationship with tissue culture banana (Musa spp.) plants and to evaluate the plants for possible harmful effects resulting from this relationship. Three Ugandan strains of B. bassiana (G41, S204 and WA) were applied by dipping the roots and rhizome in a conidial suspension, by injecting a conidial suspension into the plant rhizome and by growing the plants in sterile soil mixed with B. bassiana-colonized rice substrate. Four weeks after inoculation, plant growth parameters were determined and plant tissue colonization assessed through re-isolation of B. bassiana. All B. bassiana strains were able to colonize banana plant roots, rhizomes and pseudostem bases. Dipping plants in a conidial suspension achieved the highest colonization with no negative effect on plant growth or survival. Beauveria bassiana strain G41 was the best colonizer (up to 68%, 79% and 41% in roots, rhizome and pseudostem base, respectively) when plants were dipped. This study demonstrated that, depending on strain and inoculation method, B. bassiana can form an endophytic relationship with tissue culture banana plants, causing no harmful effects and might provide an alternative method for biological control of C. sordidus.
Keywords: Banana; Banana weevil; Beauveria bassiana